Key articles and guidelines for the emergency medicine clinical pharmacist: 2011-2018 update. (7th August 2020) - Acquisto, Nicole M; Slocum, Giles W; Bilhimer, Matthew H; Awad, Nadia I; Justice, Stephanie Baker; Kelly, Gregory F; Makhoul, Therese; Patanwala, Asad E; Peksa, Gary D; Porter, Blake; Truoccolo, Donna M Shuler; Treu, Cierra N; et al.
Abstract: Purpose: To summarize recently published research reports and practice guidelines on emergency medicine (EM)–related pharmacotherapy. Summary: Our author group was composed of 14 EM pharmacists, who used a systematic process to determine main sections and topics for the update as well as pertinent literature for inclusion. Main sections and topics were determined using a modified Delphi method, author and peer reviewer groups were formed, and articles were selected based on a comprehensive literature review and several criteria for each author-reviewer pair. These criteria included the document "Oxford Centre for Evidence-based Medicine – Levels of Evidence (March 2009)" but also clinical implications, interest to reader, and belief that a publication was a "key article" for the practicing EM pharmacist. A total of 105 articles published from January 2011 through July 2018 were objectively selected for inclusion in this review. This was not intended as a complete representation of all available pertinent literature. The reviewed publications address the management of a wide variety of disease states and topic areas that are commonly found in the emergency department: analgesia and sedation, anticoagulation, cardiovascular emergencies, emergency preparedness, endocrine emergencies, infectious diseases, neurology, pharmacy services and patient safety, respiratory care, shock, substance abuse, toxicology, and trauma. Conclusion: There are many important recent additions to the EM-related pharmacotherapy literature. As is evident with the surge of new studies, guidelines, and reviews in recent years, it is vital for the EM pharmacist to continue to stay current with advancing practice changes.